New fractional Heisenberg antiferromagnetic model and solitonic magnetic flux surfaces with normal direction - Körpınar, Talat; Körpınar, Zeliha; Demirkol, Rıdvan Cem (World Scientific, 2021)
In this paper, we study applications of fractional Heisenberg antiferromagnetic model associated with the magnetic n-lines in the normal direction. Evolution equations of magnetic n-lines due to inextensible Heisenberg antiferromagnetic flow are computed to construct the soliton surface associated with the inextensible Heisenberg antiferromagnetic flow. Then, their explicit solutions are examined in terms of magnetic and geometric quantities via the conformable fractional derivative method. Finally, we obtain new numerical fractional solutions for nonlinear fractional Schrödinger system with the inextensible Heisenberg antiferromagnetic flow model. © 2021 World Scientific Publishing Company.
Keywords: geometric phase; Heisenberg antiferromagnetic flow; Lorentz force; Magnetic field lines; magnetic flux surface